Immunological features of allergic rhinitis in combination with chronic rhinosinusitis of bacterial etiology - O. A. Kulikova; E. A. Orlova; N. I. Baranova; E. M. Kostina; O. A. Levashova (Медицинская иммунология, 2022)
Rhinitis is a socially significant and widespread disease. Often, various forms of rhinitis are combined, and thus cause severe clinical manifestations, insufficient effectiveness of drug treatment, as well as difficulties in differential diagnosis. It is known that a significant number of patients have a combination of allergic rhinitis (AR) with chronic rhinosinusitis of bacterial etiology. This condition is based on a chronic multifactorial inflammatory process of the nasal mucosa, which determines the steady progression of the disease. Of interest is the study of a number of allergo-immunological parameters in nasal secretions in order to assess local inflammation and changes in mucosal immunity in allergic rhinitis in combination with chronic rhinosinusitis of bacterial etiology (AR with HRSBE). Mucosal immunity and biological mediators determine local inflammation and pathophysiological response to etiological factors in the immunopathogenesis of AR with CRSBE. The work carried out the determination of the level of cytokines: IL-4, IL-10, TGF-â1, IFNã spontaneous and induced; immunoglobulins: IgA, IgM, IgG, sIgA in nasal secretions; leukotrienes: LT C4/ D4/E4 and LTB4 in plasma and total IgE in serum in patients with AR with moderate-severity HRSBE without exacerbation. It has been shown that the leading role in the formation of the inflammatory process in AR with CRSBE belongs to cytokines: IL-4, IL-10, TGF-â; immunoglobulins: IgM, sIgA; leukotrienes: LT C4/D4/E4 and LTB4 and total IgE. Induced cytokine production largely reflects the reserve capabilities of immunocompetent cells in response to the action of a pathogenic factor. The results obtained are associated with the persistent course of allergic and infectious inflammation and the progression of the disease. Thus, cytokines: IL-4, IL-10, TGF-â1; immunoglobulins: IgM, sIgA, IgE total and LT C4/D4/E4 and LTB4 make a significant contribution to pathogenetic mechanisms, determining the clinical course of AR with CRSBE, and can serve as biological markers of the activity of the pathological process. Undoubtedly, the immune mechanisms in the combined pathological inflammatory reaction from the mucosa in AR with HRSBE are complex and multifaceted. A personalized approach to the treatment of patients with AR with CRSBE is determined by the severity and intensity of the inflammatory reaction, as well as mucosal mucosal immunity disorders. The study of the role and significance of the production of leading cytokines, immunoglobulins in nasal secretions, as well as leukotrienes and total IgE in the blood will help the doctor in determining the tactics and duration of pharmacotherapy.